Konstruksi Kecantikan Perempuan dalam Iklan Kosmetik Jepang Hada Labo - Risa Yuliani (Chi'e: Journal of Japanese Learning and Teaching, 2022)
The Hada Labo cosmetic advert shows something different by showing a model far from the standard of physical beauty that Japanese society believes. This ad tries to represent beauty from a different angle by highlighting skin beauty and self-confidence. So the purpose of this study is to find out whether the representation of women's beauty in Hada Labo advertisements using the main female model tends to deviate and even contradict the beauty standards of Japanese society. The researcher uses Stuart Hall's representation theory approach, which uses a constructionist approach that is in line with Roland Barthes' semiotic theory so that to analyze the data, Roland Barthes' semiotic theory is used. The concept of beauty used is the concept of Naomi Wolf. So that the study results were found, namely, in this advertisement, female beauty is represented far and even better than the myth of ideal beauty standards created by the mass media and the general public today. Lack of self-confidence and the tendency to compare one's appearance with the appearance of others are things that women often do.